2014
DOI: 10.1038/srep05457
|View full text |Cite
|
Sign up to set email alerts
|

Disorganized vascular structures in sporadic venous malformations: a possible correlation with balancing effect between Tie2 and TGF-β

Abstract: Venous malformations (VMs) are among the most common slow-flow vascular malformations characterized by irregular venous channels, luminal thrombi, and phleboliths. To systematically manifest the disorganized vascular structures in sporadic VMs, we initially evaluated histopathological characteristics, perivascular cell coverage, adhesion molecules expression and vascular ultrastructures. Then, the expression of Tie2 and TGF-β in VMs was detected. Meanwhile, the in vitro studies were performed for mechanism inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 31 publications
0
41
0
Order By: Relevance
“…8,9 Pathologically, VM are composed of disorganized vessels with a thin EC lining, covered by rare, unevenly distributed SMC and poorly organized ECM. 10,11 Previous studies, including ours, have shown that markedly decreased SMC coverage is a prominent hallmark of vascular destabilization in VM, which is associated with dysregulation of perivascular ECM. 10,12 Extracellular matrix regulation involves a dynamic process balanced by ECM deposition and degradation, which is orchestrated by a variety of signal molecules and enzymes.…”
Section: Introductionmentioning
confidence: 77%
See 4 more Smart Citations
“…8,9 Pathologically, VM are composed of disorganized vessels with a thin EC lining, covered by rare, unevenly distributed SMC and poorly organized ECM. 10,11 Previous studies, including ours, have shown that markedly decreased SMC coverage is a prominent hallmark of vascular destabilization in VM, which is associated with dysregulation of perivascular ECM. 10,12 Extracellular matrix regulation involves a dynamic process balanced by ECM deposition and degradation, which is orchestrated by a variety of signal molecules and enzymes.…”
Section: Introductionmentioning
confidence: 77%
“…2,21 In contrast, VM are histologically characterized by disorganized vascular structures containing dilated vascular channels with reduced SMC coverage. 10,22 Reasonably, the characteristic paucity of surrounding vascular SMC is used as a hallmark of vascular destabilization. 10,12,23 Of note, accumulating evidence suggests that perivascular ECM, a crucial modulator of cell behavior and vascular morphogenesis, is capable of regulating proliferation, migration and differentiation of SMC.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations